Evaluation of nurse‐led social media intervention for diabetes self‐management: A mixed‐method study. Issue 5 (16th February 2022) - Kim, Su Hyun; Kim, Younghee; Choi, Sookyung; Jeon, Bomin
Abstract: Aims: This study aimed to investigate the effectiveness and understand the process of a nurse‐led social media intervention for health behavior and glucose control for diabetes self‐management among patients with type 2 diabetes mellitus. Design: This study had an explanatory sequential mixed methods design, with a randomized controlled trial and qualitative interviews. Methods: A total of 89 patients diagnosed with type 2 diabetes mellitus were randomly assigned to an intervention or a control group. Patients in the intervention group were invited to join the closed nurse‐led social media platform that included diabetes information, action planning, unmoderated chat, and questions and answers. The outcomes of diabetes self‐care behavior, hemoglobin A1c (HbA1c) percentage, fasting blood sugar level (FBS), systolic and diastolic blood pressure, and triglyceride (TG) and total cholesterol levels were measured at baseline, 3 months, and 6 months. A linear mixed model was used to analyze the effectiveness of the intervention over time. Qualitative data were collected from interviews with seven patients engaged in the intervention and analyzed using qualitative content analysis. Findings: After 6 months, insulin users who were provided with the social media intervention had significantly lower FBS and TG levels than those with usual care (135.80 ± 12.37 vs. 175.82 ± 15.34 mg/dL, p  = 0.049; 206.85 ± 38.26 vs. 387.50 ± 56.19 mg/dL, p  = 0.013; respectively). Although a similar rate of decrease in the HbA1c level over time was observed among insulin and noninsulin users after the social media intervention, this decrease was significantly greater among noninsulin users at 3 and 6 months compared with the control group (6.38 ± 0.34 vs. 7.25 ± 0.24, p  = 0.040; 6.31 ± 0.37 vs. 7.28 ± 0.26, p  = 0.036; respectively). Interview with seven patients who engaged in the intervention revealed that their engagement in the intervention was primarily determined by their acceptance of the role of managing their diabetes. Being engaged in the intervention, patients benefited from information sharing and interactive support to motivate their self‐care, nurses' professional advice to modify their behaviors, and action planning to make progress toward behavioral change. Conclusions: The positive outcomes of the nurse‐led social media intervention indicate that the social media platform is an effective strategy to implement diabetes self‐management in clinical nursing practice. Clinical Relevance: The social media intervention would be successfully implemented by nurses to facilitate patients accepting their role in diabetes management and employing key services for diabetes information, support, professional advice, and action planning.